Nurses Perceptions Abouth CPR for Patients in the Emergency Room at Santa Elisabeth Hospital Medan 2023 - Lumban Gaol, Rusmauli; Hizkia P, Indra; D.Neno, Agustina Ustin (Institute Of Computer Science (IOCS), 2024)
Background: Perception is a person's picture of an object, person and events. Each person's perception is different from one person and another. Cardiopulmonary resuscitation (CPR) is an emergency measure, in an attempt to return the state of cardiac arrest (which is known as clinical death) to a normal state, in order to prevent death. Methods: This study uses a qualitative method where data collection is carried out by interviewing 3 questions so as to be able to dig deeper into nurses' perceptions of CPR. The sampling technique used purposive sampling are 5 participants. The data analysis technique used is thematic analysis. Results: CPR is a basic life support measure for the process of stimulating, activating, and restoring circulatory and respiratory function in patients with respiratory and cardiac arrest. CPR is a quick assessment of the patient's awareness and 30:2 chest massage for 5 cycles in cardiac arrest patients who have stopped breathing. Expected. Conclusion: The research conducted by researchers on nurse perceptions about CPR is good but needs to be improved by conducting training to increase nurses' knowledge of nurses' perceptions of CPR in the Emergency Room (IGD) at Santa Elisabeth Hospital Medan in 2023.